Mitigation of the Biofilm Using Nanoparticles By Enhanced by D-alanine and D-proline - Fakhri Alajeeli (Institute of Medico-legal Publications Pvt Ltd, 2021)
The present study was undertaken to investigate the susceptibility patterns as antifungal and growth of certainD-amino acids inhibitory effects, includes D-alanine(D-ala) and D-proline (D-pro). The obtained resultsindicated that D- proline acid is potent mostly as antifungal, among tested D-amino acids, then followedby D-ala. The study aim was evaluating the of D-amino acids and nanoparticles against Candida albicansadhered cells and bio-films. Results showed that D-ala MIC value was 25 ?g/ml, while in methods of TCP,(D-pro) MIC 50 ?g/ml value. Nanoparticles (lithium and silver) and amino acids (D-pro and D-ala) effectin preventing cells adhesion on polystyrene surface and mature bio-film inhibition was studied. Highestinhibition was obtained at D-pro concentration 50 ?g /ml, while the lowest at concentration D-ala 25 ?g /mlagainst mature bio-film and cell adhesion.